The number in the parenthesis will be your x value so you can just plug them in the equation given to you and solve.
In number 1, g(x) = -5x + 2. 1a gives you g(-1). That -1 inside that g(-1) will be your x.
g(-1) = -5(-1) + 2
g(-1) = 5 + 2
g(-1) = 7
For 1b, you have g(-2) so you plug -2 everywhere the x is.
g(-2) = -5(-2) + 2
g(-2) = 12
For 3a, you have a different equation: x^2 + 4x - 1 and you have g(-4). Not a problem though just plug -4 into all the places x is at and solve.
g(-4) = -4^2 + 4(-4) - 1
= 16 - 16 - 1
= -1
Hope this helped